The economic effects of net nominal protection coefficients for meat products in Iraq - Man, Norsida; Hussein, Sarmad Ali; Latif, Ismail; Kamarulzaman, Nitty Hirawaty (Asian Research Publishing Network (ARPN), 2015)
The research aims to release the effects of price policy for meat products in Iraq through the net nominal protection coefficients whether for the benefit of producers or consumers and measure the net nominal protection coefficient aggregate for all meat products combined. Finding ensure goods (Beef, Poultry, Fish), which are important food commodities in the lives of citizens; it is seen that a continuing rise in commodity prices, especially in recent years, which could harm the consumption of these products. The results showed that the producers Beef meat obtained the largest share of protection for fish and poultry producers. In general protection during the nineties was for the benefit of consumers and after the 2004-2010 year was protection for the benefit of producers of all types of meat. This was reflected on the values of synthesis protection coefficient of meat all. Iraqi currency exchange rates had a role in the price policy. The study advises advancement by animal production and improves the methods and techniques and provides output elements.